Understanding the factors affecting duration in answering MCQ examination: The students’ perspective - Chatchai Kreepala; Srunwas Thongsombat; Krittanont Wattanavaekin; Taechasit Danjittrong; Nattawut Keeratibharat; Thitikorn Juntararuangtong (The Asia Pacific Scholar)
Introduction: Factors affecting decision-making duration in MCQs can enhance assessment effectiveness, ensuring they accurately measure the intended objectives and address issues related to incomplete exams due to time constraints. The authors aimed to explore the aspects of medical student’s perspective regarding the factors influencing their decision making on MCQ assessments. Methods: A mixed-methods explanatory sequential design was utilised. Initial surveys were conducted using percentages, mean and non-parametric analysis obtained via online questionnaires from the sample group: all 2nd - 5th year medical students from SUT, Thailand. The validity of the questionnaires was verified by three independent reviewers (IOC=0.89). This was followed by semi-structured group interviews to explore student’s perspective on the factors affecting their decision. Qualitative analysis was conducted to explore detailed information until data saturation was achieved. Results: Data from the quantitative analysis identified four factors that students believe affect the duration of the exam: the total word count of each question, test difficulty, and images in tests. Meanwhile, the qualitative analysis provided additional insights on factors such as the examination atmosphere affecting their decisions. Conclusion: This report indicated that data acquired from a comprehensive reading question should be distinguished from those requiring decisive reading. Apart from text length, question taxonomy-such as recall or application- and questions with given images and tables should be considered as factors determining time allocation for an MCQ. Future research based on these results should aim to develop a mathematical formula to calculate exam duration, accounting for question difficulty and length.